Characterization of a nose-only inhaled phosgene acute lung injury mouse model. (6th December 2015) - Plahovinsak, Jennifer L.; Perry, Mark R.; Knostman, Katherine A.; Segal, Robert; Babin, Michael C.
Abstract: Context : Phosgene's primary mode of action is as a pulmonary irritant characterized by its early latent phase where life-threatening, non-cardiogenic pulmonary edema is typically observed 6‐24 h post-exposure. Objective : To develop an inhaled phosgene acute lung injury (ALI) model in C57BL/6 mice that can be used to screen potential medical countermeasures. Methods : A Cannon style nose-only inhalation exposure tower was used to expose mice to phosgene (8 ppm) or air (sham). An inhalation lethality study was conducted to determine the 8 ppm median lethal exposure (LCt50 ) at 24 and 48 h post-exposure. The model was then developed at 1.2 times the 24 h LCt50 . At predetermined serial sacrifice time points, survivors were euthanized, body and lung weights collected, and lung tissues processed for histopathology. Additionally, post-exposure clinical observations were used to assess quality of life. Results and discussion : The 24-hour LCt50 was 226 ppm*min (8 ppm for 28.2 min) and the 48-hour LCt50 was 215 ppm*min (8 ppm for 26.9 min). The phosgene exposed animals had a distinct progression of clinical signs, histopathological changes and increased lung/body weight ratios. Early indicators of a 1.2 times the 24-hour LCt50 phosgene exposure were significant changes in the lung-to-body weight ratios by 4 h post-exposure. The progression of clinical signs and histopathological changes were important endpoints for characterizing phosgene-induced ALI for future countermeasure studies. Conclusion : An 8 ppm phosgene exposure for 34 min (1.2 × LCt50 ) is the minimum challenge recommended for evaluating therapeutic interventions. The predicted higher mortality in the phosgene-only controls will help demonstrate efficacy of candidate treatments and increase the probability that a change in survival rate is statistically significant.